Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1117/12.621889
|View full text |Cite
|
Sign up to set email alerts
|

<title>Use of LANDSAT-7 ETM+ with ancillary data for soil salinity mapping in northeast Thailand</title>

Abstract: Soil salinity is a major environmental constraint in Northeast Thailand. Sustainable land use and management in this region require careful mapping of the salinity status. This study was conducted to investigate performances of some digital classification techniques for soil salinity mapping in the Northeast. The techniques investigated were based on the use of LANDSAT-7 ETM+ with different combinations of three kinds of ancillary data (i.e., topography, geology, and underground water quality). In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 4 publications
1
10
0
1
Order By: Relevance
“…Their results indicated that the use of Landsat TM imagery effectively identified bare soils that were characterized by high spectral reflectance due to a high salt content on the surface, and the approach of integrating DTA with remote sensing data was more accurate and effective compared to using remote sensing analysis alone. Many researchers, including Katawatin and Kotrapat [52], Mehrjardi [53] and Yu et al [54] have investigated the utility and effectiveness of ETM+ data for soil salinity mapping and monitoring. For example, in Thailand, Katawatin and Kotrapat [52] investigated the use of Landsat-7 ETM+ with different combinations of three sources of ancillary data (topography, geology, and underground water quality) for soil salinity mapping.…”
Section: Multispectral Satellite Sensors For Mapping and Monitoring Smentioning
confidence: 99%
See 1 more Smart Citation
“…Their results indicated that the use of Landsat TM imagery effectively identified bare soils that were characterized by high spectral reflectance due to a high salt content on the surface, and the approach of integrating DTA with remote sensing data was more accurate and effective compared to using remote sensing analysis alone. Many researchers, including Katawatin and Kotrapat [52], Mehrjardi [53] and Yu et al [54] have investigated the utility and effectiveness of ETM+ data for soil salinity mapping and monitoring. For example, in Thailand, Katawatin and Kotrapat [52] investigated the use of Landsat-7 ETM+ with different combinations of three sources of ancillary data (topography, geology, and underground water quality) for soil salinity mapping.…”
Section: Multispectral Satellite Sensors For Mapping and Monitoring Smentioning
confidence: 99%
“…Many researchers, including Katawatin and Kotrapat [52], Mehrjardi [53] and Yu et al [54] have investigated the utility and effectiveness of ETM+ data for soil salinity mapping and monitoring. For example, in Thailand, Katawatin and Kotrapat [52] investigated the use of Landsat-7 ETM+ with different combinations of three sources of ancillary data (topography, geology, and underground water quality) for soil salinity mapping. A maximum likelihood classification method was employed in this study.…”
Section: Multispectral Satellite Sensors For Mapping and Monitoring Smentioning
confidence: 99%
“…Their results indicated that the use of Landsat TM imagery effectively identified bare soils that were characterized by high spectral reflectance due to a high salt content on the surface, and the approach of integrating DTA with remote sensing data was more accurate and effective compared to using remote sensing analysis alone. Katawatin and Kotrapat (2004) investigated the utility and effectiveness of Landsat-7 ETM+ data with different combinations of three sources of ancillary data (topography, geology, and underground water quality) for soil salinity mapping and monitoring. Their results showed that the use of Landsat ETM+ data bands 4, 5 and 7 yielded the most accurate soil salinity map, with 83.6% overall accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…They found that there was a significant relationship between EC values and reflectance in Landsat bands 1, 2, 3 and 4. Katawatin and Kotrapat (2005), Mehrjardi et al (2008) and Yu et al (2010) have investigated the utility and effectiveness of ETM+ data for soil salinity mapping and monitoring. Katawatin and Kotrapat (2005) investigated the use of Landsat-7 ETM+ with different combinations of three sources of ancillary data for soil salinity mapping.…”
Section: Resultsmentioning
confidence: 99%